2012
DOI: 10.1097/prs.0b013e31822b6932
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant plus Ondansetron Compared with Ondansetron Alone in Reducing Postoperative Nausea and Vomiting in Ambulatory Patients Undergoing Plastic Surgery

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 0 publications
0
46
0
3
Order By: Relevance
“…Aprepitant has already proved to be effective in the prevention of PONV in some studies [16][17][18]. We previously reported that orally administered aprepitant was also effective in decreasing the incidence of PONV after laparoscopic gynecological surgery [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aprepitant has already proved to be effective in the prevention of PONV in some studies [16][17][18]. We previously reported that orally administered aprepitant was also effective in decreasing the incidence of PONV after laparoscopic gynecological surgery [19].…”
Section: Discussionmentioning
confidence: 98%
“…Gan et al [21] also determined that aprepitant and ondansetron had similar preventive effects on postoperative nausea, but aprepitant was more effective in the prevention of vomiting than ondansetron in a study comparing the two drugs. Recently, Vallejo et al [18] reported that the addition of aprepitant to ondansetron significantly decreased postoperative vomiting rates and nausea severity for up to 48 h after plastic surgery. These results suggest that aprepitant prevents PONV by decreasing the vomiting rate and is not adequate for the complete prevention of postoperative nausea.…”
Section: Discussionmentioning
confidence: 99%
“…1 Patient-specific risk factors include female gender, nonsmoking status, and a history of PONV and/or motion sickness. 2,4,5 Anesthetic considerations include use of volatile agents, nitrous oxide, and postoperative opioids. 2,6 Surgery-related elements, such as the duration and type of surgery, are also of special concern (Table 1).…”
mentioning
confidence: 99%
“…1,4 Unfortunately, common antiemetics used today tend to have a limited duration of action, variable reliability, and may reduce overall incidence of PONV by only 26%. 5,9 For this reason, there is a need to develop and use medications that act at a different receptor, have a prolonged effect, and have minimal adverse side effects in prevention of PONV.…”
mentioning
confidence: 99%
See 1 more Smart Citation